Coordinate Monitoring Technology in the Process of Incremental Launching Construction of Curved Steel Box Girder Bridge - Haipeng Wang; Kai Wang; Nan Guo (Advances in Civil Engineering)
Based on the steel box girder curve incremental launching project of SW ramp bridge in Harbin East Third Ring Road, the geometric alignment and structural internal force of the steel box girder during the incremental launching process were monitored in the whole process. The curve incremental launching coordinate position control method was adopted, and the relevant parameters were modified according to the site construction situation and the initial stress conditions of the girders, and the corrected theoretical value was used as the control and evaluation basis of the monitoring value. The results showed that the original theoretical deflection value was −33.10 mm, the modified theoretical deflection value was −64.10 mm, and the actual monitoring value was −53.20 mm. The modified theoretical value agreed well with the monitoring value, and the error rate between the monitoring value and the theoretical value under each working condition was −17.82%∼14.48%. The geometric alignment and internal force of the steel box girder met the monitoring requirements, ensuring that the steel box girder can meet the design requirements under various working conditions.